2009
DOI: 10.3748/wjg.15.2376
|View full text |Cite
|
Sign up to set email alerts
|

Local anesthesia with ropivacaine for patients undergoing laparoscopic cholecystectomy

Abstract: AIM:To investigate the effect of pain relief after infusion of ropivacaine at port sites at the end of surgery. METHODS:From October 2006 to September 2007, 72 patients undergoing laparoscopic cholecystectomy (LC) were randomized into two groups of 36 patients. One group received ropivacaine infusion at the port sites at the end of LC and the other received normal saline. A visual analog scale was used to assess postoperative pain when the patient awakened in the operating room, 6 and 24 h after surgery, and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
5

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 17 publications
1
33
0
5
Order By: Relevance
“…4 Pain is the most frequent complaint after laparoscopic cholecystectomy and the main reason for staying overnight at hospital on the day of operation. 5 Pain after laparoscopic cholecystectomy depends on multiple factors including rupture of blood vessels caused by rapid distension of the peritoneum, traumatic traction on the nerves, trauma to the abdominal wall during port insertion and GB retrieval and pneumoperitoneum created by use of CO2 to maintain high abdominal pressure. 5 It is reported that incisional pain is more intense than visceral pain and is dominant during the first 48 hours after laparoscopic cholecystectomy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Pain is the most frequent complaint after laparoscopic cholecystectomy and the main reason for staying overnight at hospital on the day of operation. 5 Pain after laparoscopic cholecystectomy depends on multiple factors including rupture of blood vessels caused by rapid distension of the peritoneum, traumatic traction on the nerves, trauma to the abdominal wall during port insertion and GB retrieval and pneumoperitoneum created by use of CO2 to maintain high abdominal pressure. 5 It is reported that incisional pain is more intense than visceral pain and is dominant during the first 48 hours after laparoscopic cholecystectomy.…”
Section: Introductionmentioning
confidence: 99%
“…5 Pain after laparoscopic cholecystectomy depends on multiple factors including rupture of blood vessels caused by rapid distension of the peritoneum, traumatic traction on the nerves, trauma to the abdominal wall during port insertion and GB retrieval and pneumoperitoneum created by use of CO2 to maintain high abdominal pressure. 5 It is reported that incisional pain is more intense than visceral pain and is dominant during the first 48 hours after laparoscopic cholecystectomy. 6 Retrieval of GB is an important terminal event of laparoscopic cholecystectomy and is thought to be one of the factors affecting postoperative port site pain and infection.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 The longer duration of hospitalization in our study can be attributed to other factors related to the surgery, i.e. all patients are inserted abdominal drains as a standard protocol & in our wards removal of the drain is done at the 2 nd to 3 rd day post operatively.…”
Section: Duration Of Hospitalizationmentioning
confidence: 96%
“…Y. Liu и соавт. (2009) у части паци-ентов вводили 20 мл 1% раствора ропивакаина после наложения кожных швов, после чего статистически значимые различия с группой сравнения отсутство-вали [140]. А вот N. Hasaniya и соавт.…”
Section: рис 8 манипуляции «ловкого» мини-робота при трансгастральнunclassified